Increasing Science Literacy through Make a Match Learning Media on Human Growth Materials in Class V of Elementary School - Tazkya Gina Izzati; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to evaluate the influence of the Make a Match learning method on the science literacy ability of grade V elementary school students. This method is compared to conventional learning approaches in improving students' understanding of science materials. The research method used is an experiment using the Rasch Model to analyze the difficulty level of pretest and posttest questions. The results showed that there was a significant improvement in the science literacy ability of students in the experimental class who used the Make a Match method compared to the control class. However, there are several questions that are still considered difficult by students in both groups. This finding highlights the need to adjust learning strategies to overcome these difficulties to improve students' understanding of science literacy.